Analisis Peramalan Permintaan dan Pengendalian Persediaan Bahan Baku Body Scrub Powder di CV. Denara Duta Mandiri - Cahyadewi, Desya Rachmasari; Wiranatha, A.A.P. Agung Suryawan; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This study aims to analyze the demand forecasting of body scrub powder products in October 2019 and the level of raw material inventory body scrub powder optimal in order to minimize the total cost of inventory in CV. Denara Duta Mandiri. Forecasting analysis using time series model with 3 methods of Moving Averages with 2, 3 and 4 month time period, exponential smoothing method with ? = 0.1, ? = 0.5, ? = 0.9 and Trend Projection. To analyze the value of forecasting accuracy, the method used are Mean Absolute Deviation (MAD) and Mean Squared Error (MSE). The results show that the Trend Projection method is the most effective method that can be used as the basis for determine body scrub powder products demand, with the result of forecasting demand is 562 kg and the value of forecasting accuracy,  MAD = 76,97, MSE = 9.760,12. The results of Economic Order Quantity (EOQ) showed that total cost of raw material inventory control body scrub powder at CV. Denara Duta Mandiri by using EOQ smaller than the methods used by the company. CV. Denara Duta Mandiri management should try to apply the EOQ method in terms of supply of raw materials so that the company can better minimize inventory costs. Keywords : demand forecasting, raw material, Economic Order Quantity (EOQ)